Construction of bismuth-based porous carbon models by 3D printing technology for light-enhanced removal of chloride ions in wastewater. (15th October 2022) - Jiang, Haiwei; Huang, Shouqiang; Lv, Hongying; Ge, Dongdong; He, Xu; Zhou, Pin; Xiao, Kun; Zhang, Yaheng
Highlights: Porous carbon model achieved by 3D printing is used as the chloride removal agent. Bi 0 /Bi2 O3 core/shell nanoparticles are tightly adhered to the porous carbon model. The light-driven chloride removal efficiency is 2.3 times that in the dark. The holes generated cause photocorrosion of Bi 0 and Bi2 O3 to release more Bi 3+ ions. Cl is converted from hole, OH, and O2 − to assist the formation of BiOCl. Abstract: The bismuth oxide (Bi2 O3 ) based chloride (Cl − ) removal method is one of the chemical precipitation methods possessing good selectivity and high removal efficiency of Cl − ions, but Bi2 O3 often appears in the powder form, which is difficult to be recovered for regeneration. In this work, the combination of 3D printing technology and the Bi2 O3 method was explored to construct the resin model including the Bi-precursors. In the optimum carbonization process at 400 °C for 30 min, the Bi 3+ ions of the Bi-precursor were reduced into the metallic Bi 0 nanoparticles, whose surfaces were covered by the thin Bi2 O3 layers to form the heterostructured Bi 0 /Bi2 O3 core/shell nanoparticles with an average size of 43 nm. These Bi 0 /Bi2 O3 nanoparticles were tightly adhered to the internal and external surfaces of the hierarchical porous carbon model (Bi-PCM), which greatly facilitated their regeneration and ensured the stable Cl − removal performance. After five cycles of Cl − removal, the chloride removal efficiency over the multiple Bi-PCMs in the dark and pH 1 conditions maintained at about 26%, which then largely increased to 63.6% with UV light irradiation. The light-enhanced mechanism was related to the improved release rate of Bi 3+ ions caused by photocorrosion and the Cl radicals produced from the holes and the OH and O2 − radicals, which quickly reacted with Bi2 O3 to form BiOCl. The construction of Bi-PCMs by using 3D printing technology provides a very promising strategy for the removal of Cl − ions from wastewater. Graphical abstract: Image, graphical abstract